PELAKSANAAN FUNGSI DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KABUPATEN DAIRI PERIODE 2014-2019 DALAM BIDANG LEGISLASI - Heraldo Zinggra; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to describe and analyze critically and sociologically aboutthe Implementation of the Function of the Regional House of Representatives(DPRD) Period 2014-2019 in Legislation. The results of this study are expected tobe used as the motivation of members of the Regional House of Representatives(DPRD) Dairi District Period 2014-2019 in Legislation. This research is a fieldresearch using qualitative descriptive analysis by taking research subjects ofDairi Regency DPRD period 2014-2019. Data collection is done by interviewmethod, observation and documentation. The results of this study indicate thatmembers of Parliament Dairi period 2014-2019 very important role in theimplementation of the legislative function of the Regional House ofRepresentatives (DPRD). Phase by the Regional People's Representative Councilof Dairi Regency peridoe 2014-2019 in establishing the Regional Regulation(Perda) consists of; Planning phase, Preparation stage, Preparation technique,Formulation phase, Discussion phase and Legal phase. The relevance of thematerial principle of the Regional Regulation (Perda) in the implementation ofthe legislative function of the Regional House of Representatives of Dairi Regencyfor the period 2014-2019 consists of; Absorb the aspirations of society, Initiativesand Initiatives, Public Interest and In accordance with the rule of law. Therealization of the legislative function of Dairi District People's RepresentativeCouncil (DPRD) in 2014-2019 period is hampered by several obstacles but hasbeen made by Dairi District People's Representative Council 2014-2019 toimprove the implementation of legislation function.Keywords: DPRD, Legislation Function, Regional Regulation (Perda).